Facebook Use and Political Participation: The Impact of Exposure to Shared Political Information, Connections With Public Political Actors, and Network Structural Heterogeneity. (December 2013) - Tang, Gary; Lee, Francis L. F.
Some recent studies have illustrated a positive relationship between social media use and political participation among young people. Researchers, however, have operationalized social media usage differently. This article adopts a multidimensional approach to the study of the impact of social media. Focusing on Facebook (FB), the most widely utilized social networking site in Hong Kong, this study examines how time spent on FB, exposure to shared political information, network size, network structural heterogeneity, and direct connection with public political actors relate to young people's online and offline political participation. Analysis of a survey of university students ( N = 774) shows that participation is explained most prominently by direct connection with public political actors, followed by exposure to shared political information. These two variables also mediate the impact of other dimensions of FB use on political participation.